Doppler-Based Ground Speed Sensor Fusion and Slip Control for a Wheeled Rover - Lhomme-Desages, D.; Grand, C.; Guinot, J.-C.; Ben Amar, F. (IEEE/ASME transactions on mechatronics, 2009)
High-speed unmanned ground vehicles evolving on natural terrains can exhibit a significant slip and skid. An estimation of both friction and traction forces can allow to achieve a better control. In order to implement a control architecture based on the vehicle dynamic model and the wheel-soil interaction model, the knowledge of the wheels slip rate is required. The wheel angular velocities can be precisely measured. But the true measurement of the ground speed of the vehicle is much more challenging. A low-cost Doppler radar is used, in conjunction with an accelerometer, to obtain the ground speed. Thus, the knowledge of the slip rate allows us to setup an in situ procedure for the estimation of soil parameters that is based on the measurement of the motors torques. A wheel slippage controller has also been implemented, which is a first step toward high-level dynamic control.